FORMULASI SEDIAAN DAN UJI ORGANOLEPTIK MASKER DAUN KELOR (Moringa oleifera Lam) dan PATI BENGKUANG (Pachyrhizus erosus.L) UNTUK PERAWATAN KULIT BERJERAWAT - Pramudita, Endah; Puspariki, Jenta; Suharti, Suharti (Sekolah Tinggi Ilmu Kesehatan Holistik, 2019)
Background: Acne treatment using antibacterial has side effects such as irritation and indirect organ damage [1]. Therefore we need other alternatives for safer use of natural ingredients. Natural materials that can be used are usually derived from medicinal plants, vegetables and fruits. [2] Considering the superiority of moringa (Moringa oleifera Lam) and yam (Pachyrhizus erosus.L) leaves that both contain efficacious compounds for facial skin care, researchers are interested in conducting research by making mask preparations for Moringa leaf extract and yam starch. Research Objectives: making moringa leaf and yam starch preparations which can be taken anywhere practically. Method: This research uses the Action Research method with three formulations with different ratio of Moringa leaf extract and yam starch, F1 (3gr: 7gr), F2 (2.5gr: 7.5gr) and F3 (2gr: 8gr) . Results: Organoleptic test results of Moringa oleifera Lam (Moringa oleifera) mask and yam (Pachyrhizus erosus.L) mask masks which have been tested and observed for 3 weeks showed that there were no significant changes. The results of pH tests conducted for 3 weeks showed the results of pH at F1 (3gr: 7gr), F2 (2.5gr: 7.5gr) and F3 (2gr: 8gr) were relatively stable at around 5. Conclusion: From the pH test which is done once a week it shows a stable pH result which is around 5, in accordance with normal face pH around 4.5-6.5. Organoleptic test results performed on the three formulations did not show significant changes. Changes are only found in the distinctive aroma of Moringa leaf extract, this is due to the addition of Moringa leaf extract to each formulation with different amounts.